Oligodendrocyte precursors gain Schwann cell‐like phenotype and remyelinate axons upon engraftment into peripheral nerves. (30th July 2019) - Mi, Ruifa; Tammia, Markus; Shinn, Daniel; Li, Ying; Martin, Russell; Mao, Hai‐Quan; Höke, Ahmet
Abstract: The ability to treat large peripheral nerve injuries may be greatly advanced if an accessible source of human myelinating cells is identified, as it overcomes one of the major limitations of acellular or synthetic nerve guides compared with autografts, the gold standard for large defect repair. Methods to derive oligodendrocyte precursor cells (OPCs) from human pluripotent stem cells have advanced to the point where they have been shown capable of myelination and are being evaluated in clinical trials. Here, we test the hypothesis that OPCs can survive and remyelinate axons in the peripheral nervous system during a repair process. Using freshly isolated OPCs from mouse post‐natal brains, we engrafted these OPCs into the tibial nerve immediately after it being subjected to cryolesioning. At 1‐month postengraftment, we found numerous graft‐derived cells that survived in this environment, and many transplanted cells expressed Schwann cell markers such as periaxin and S100β coexpressed with myelin basic protein, whereas oligodendrocyte markers O4 and Olig2 were virtually absent. Our results demonstrate that OPCs can survive in a peripheral nervous system micro‐environment and undergo niche‐dependent transdifferentiation into Schwann cell‐like cells as has previously been observed in central nervous system focal demyelination models, suggesting that OPCs constitute an accessible source of cells for peripheral nerve cell therapies.